Epidemiological Determinants of Mental Well-Being and Quality of Life among Homemakers with Hypertension: A Cross-Sectional Analysis - Bidnurmath, Ashwini Shivakumar (Indian J Community Med, 2020)
BACKGROUND: Stress is a major contributor to the physiology of hypertension (HTN) and is linked closely to mental well-being and overall quality of life (QoL). Health issues pertaining to women's health have usually focused on reproduction, while mental well-being has largely been neglected. OBJECTIVES: The objective of the study was to assess the perceived stress and QoL among homemakers with HTN. MATERIALS AND METHODS: A community-based cross-sectional study was carried out, among 426 homemakers with HTN residing in Udupi, Karnataka. The sociodemographic and disease characteristics, Cohen's Perceived Stress Scale-10, World Health Organization QoL Brief Questionnaire (WHOQOL-BREF), anthropometry, and vitals were measured. RESULTS: Of the study participants, 245 (57.5%) were aged ≤60 years and 317 (74.4%) had been diagnosed with HTN in the past decade. Low and high perceived stress was seen among 306 (71.8%) and 120 (28.2%) women, respectively. Among the four domains of WHOQOL-BREF, the physical domain had the highest mean (±standard deviation) score of 67.44 (±16.50), whereas the lowest score of 54.49 (±19.75) was observed in the social domain. The odds of high stress among single women and those with a pill burden of >2/day were 1.93 (P=0.004, 95% CI=1.228, 3.054) and 1.77 (P=0.038, 95% CI CI=0.962, 3.270) respectively. The QoL was significantly better among those aged <60 years, married, and literate women. CONCLUSIONS: Mental well-being among the hypertensive homemakers was good, with low perceived stress and high mean scores of QOL domains.